Activity measurements of the radionuclides (18)F and (64)Cu for the NIST, USA in the ongoing comparisons BIPM.RI(II)-K4.F-18 and BIPM.RI(II)-K4.Cu-64 - Michotte, C. (Metrologia, 2017)
In 2016, comparisons of activity measurements of (18)F and (64)Cu using the Transfer Instrument of the International Reference System (SIRTI) took place at the National Institute of Standards and Technology (NIST, USA). This is the first SIRTI comparison for (64)Cu. Ampoules containing about 27 kBq of (18)F and 100 kBq of (64)Cu solutions were measured in the SIRTI for about 5 and 1.5 half-lives, respectively. The NIST standardized the activity in the ampoules by ionization chamber measurements traceable to 4π(LS)β−γ anticoincidence measurements. The comparisons, identifiers BIPM.RI(II)-K4.F-18 and BIPM.RI(II)-K4.Cu-64, are linked to the corresponding BIPM.RI(II)-K1.F-18 and BIPM.RI(II)-K1.Cu-64 comparisons and degrees of equivalence with the respective key comparison reference values have been evaluated. The NIST replaces its earlier degree of equivalence for (18)F obtained in the frame of the CCRI(II)-K3.F-18 comparison in 2001.